Horse, harness and horse-drawn wagon in Eastern Uzh Romani - Beníšek, Michael (Romano džaniben, 2022)
This paper describes the Romani lexicon for the use of horse and horse-drawn wagon in varieties of the Eastern Uzh dialect region, which is located in the west of the Transcarpathian region of Ukraine and is part of North Central Romani. The article, based on first-hand fieldwork data of the author, presents the terms for horse and the cultural terminology for the use of horse, namely the lexicon related to horse riding, harnessing and stabling. Relatively detailed attention is also paid to the terminology for horse-drawn wagon and its parts, including the wheel, as well as to the term for wagoner. The analysis of the origins of the discussed terms shows that most of the terms are recent loanwords from East Slavic and partly Slovak dialects or from Hungarian and (indirectly) German, while only names for some very basic concepts have been preserved from the Proto-Romani heritage. The study includes a glossary of all the analysed Eastern Uzh Romani words.